2017
DOI: 10.15208/beh.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate volatility and financial performance of agriculture firms in Malaysia: An empirical analysis using GARCH, wavelet and system GMM

Abstract: The insurgence of exchange rate volatility over the years has gained the attention of not only scholars but also policy makers around the world. This paper investigates the influence of exchange rate volatility to the financial performance of agriculture firms in Malaysia. Authors use the system GMM dynamic panel techniques, wavelet coherence technique and GARCH (1, 1) for the period of 2001 and 2015. The findings show that the volatility of exchange rate of Malaysian Ringgit (RM) has a negative impact on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The calculation is done using the Johansen cointegration process and the dynamic ordinary least squares (DOLS) estimator. Reaz et al (2017) showed that the volatility of the exchange rate harmed the financial output of Malaysian agriculture firms from 2001 to 2015.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The calculation is done using the Johansen cointegration process and the dynamic ordinary least squares (DOLS) estimator. Reaz et al (2017) showed that the volatility of the exchange rate harmed the financial output of Malaysian agriculture firms from 2001 to 2015.…”
Section: Literature Reviewmentioning
confidence: 99%